Social Capital and Educational Resilience among University Students in Post-Pandemic Contexts - Oraekesi Stella Chioma; Ngwoke Celestine Ikechukwu (International Journal of Social Sciences, Language, and Education, 2026)
The post-pandemic landscape of higher education has intensified concerns regarding university students’ capacity to adapt to prolonged academic, psychological, and social disruptions. This study explores the role of social capital in shaping educational resilience among university students in post-pandemic contexts through an integrative conceptual analysis of recent scholarly literature. Drawing on socio-ecological and resilience-based frameworks, the study synthesizes empirical findings from international research to examine how peer networks, institutional trust, and community relationships contribute to students’ adaptive academic functioning. The analysis reveals that social capital operates as a foundational mechanism that mediates psychological well-being, academic engagement, and persistence amid post-pandemic challenges. Institutional environments characterized by relational support, inclusive governance, and collaborative learning cultures are shown to strengthen resilience outcomes, while unequal access to social capital exacerbates academic vulnerability. The study concludes that educational resilience should be understood as a socially embedded and structurally supported process rather than an individual attribute. These findings underscore the importance of relationally oriented policies and institutional strategies in fostering sustainable resilience within post-pandemic higher education systems.